2015
DOI: 10.1016/j.ibmb.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrase generates a pH gradient in Bombyx mori silk glands

Abstract: Silk is a protein of interest to both biological and industrial sciences. The silkworm, Bombyx mori, forms this protein into strong threads starting from soluble silk proteins using a number of biochemical and physical cues to allow the transition from liquid to fibrous silk. A pH gradient has been measured along the gland, but the methodology employed was not able to precisely determine the pH at specific regions of interest in the silk gland. Furthermore, the physiological mechanisms responsible for the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 44 publications
1
68
0
Order By: Relevance
“…Nevertheless, the present work revealed no direct correlation between the hemolymph pH and the measured viscosity, as shown in Figure b. Moreover, the pH of the feedstock appeared to remain roughly neutral (6.5 to 7.2), in agreement with previous work and suggesting that the gland contents are insulated from changes in the hemolymph.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Nevertheless, the present work revealed no direct correlation between the hemolymph pH and the measured viscosity, as shown in Figure b. Moreover, the pH of the feedstock appeared to remain roughly neutral (6.5 to 7.2), in agreement with previous work and suggesting that the gland contents are insulated from changes in the hemolymph.…”
Section: Resultssupporting
confidence: 81%
“…Based on the published amino acid sequence, fibroin is believed to contain small proportions of phenolic, carboxylic acid, or amine substituents in the side‐groups (≈5.2, 1.4, and 0.9 mol%, respectively). Previous work has suggested that interactions between these groups are sensitive to pH, thereby affecting the fibroin chain conformation and viscosity . Indeed, rheological changes brought about by exposing silk feedstock to ethanoic acid or ammonia vapors have previously been reported by Terry et al …”
Section: Resultsmentioning
confidence: 94%
“…[8][9][10][11] A factor known to regulate silk assembly is the decrease in pH along the duct, caused by carbanhydrase production and proton pumps. [12][13][14] It is also suggested that ion concentration gradients, dehydration of the protein dope, and hydrodynamic forces that increase along the narrowing duct facilitate the fiber formation. 4,11,[15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…As stored in the gland lumen, H-fibroins lack b-sheet secondary structure, occupying instead mostly type II b-turn and random coil conformations, a form referred to as silk I (12,13). At the relatively high pH (6.9-8.0) in the posterior silk gland lumen, like-charge repulsion between the negatively charged termini and short, negatively charged spacers interspersed in the poly(GA) central region is thought to maintain the silk I conformation and the colloidal fluid form of the silk complexes (11,14,15). Fiber formation begins as the fluid silk dope is sheared through the tapered anterior gland with a coincident drop in pH from 6.9 to 4.8 (11).…”
mentioning
confidence: 99%